Penggunaan Deiksis Persona dalam Novel Saat-Saat Jauh Karya Lia Seplia - Situmorang, Netti Yuliana; Charlina, Charlina; Burhanudin, Dudung (Universitas Tidar, 2024)
Language is a tool for communication and interaction between humans, both individuall and in groups every day. Smooth human interaction and communication depends on the use of language that is appropriate to the situation and conditions of the speaker and listener, as well as the appropriate method of delivery. Therefore, communication activities are greatly influenced by factors such as the interlocutor, the speaker's goals, the situation and the topic of conversation. This use of language while still paying attention to context is known as pragmatics. The deictic system is an aspect of language that supports communication because it requires understanding the context or situation of the conversation. The phenomenon of deixis is the most appropriate way to show the relationship between language and context in the structure of the language itself. This research aims to analyze the types and forms of persona deixis in the novelSaat- saatjauh by Lia Seplia. The research method in this research is qualitative research using a literature review. The research results show that in the novel there are 581 persona deixis data. The data is divided based on type, namely first person deixis totaling 273 data, second person deixis totaling 225 data, and third person deixis totaling 83 data. Apart from that, the data is also divided based on its form, such as 217 singular first person deixis data, 29 plural first person deixis data, 217 single second person deixis data, 8 plural second person deixis data, 58 singular third person deixis data, and plural third person deixis as many as 25 data .